Higher lactate for better performance? A longitudinal case study of a highly trained female swimmer - Kabasakalis, A.; Karga, M.-R.; Mougios, V. (International Journal of Sports Physiology and Performance, 2026)
Purpose: To longitudinally investigate the relationship of blood lactate concentration (BLC) and performance in the 50- and 100-m backstroke swimming events of a highly trained female swimmer. Methods: We gathered BLC and performance data from 18 50-m and 24 100-m backstroke races of a highly trained national-level female swimmer over 6 years (age 14-20). We measured BLC with a portable analyzer and calculated swimming speed from the official results. We checked the data distribution with the Shapiro-Wilk test and performed Pearson correlation analysis, followed by partial correlation analysis. We used Student t test for independent observations to compare BLC between the 2 events. Statistical significance was declared at P < .05. Results: The BLC was 15.5 (2.7) mmol·L-1 (mean [SD] throughout) after the 50-m races and 16.5 (1.8) mmol·L-1 after the 100-m races. No significant difference was found in BLC between the 2 events (P = .127). We found a significant correlation between BLC and swimming speed at both 50 m (P = .018, r = .548) and 100 m (P = .012, r = .503), as well as between age and speed at 50 m (P = .001, r = .721) and between age and BLC at 100 m (P = .039, r = .424). When controlling for age, BLC and speed correlated significantly at 100 m (P = .034, r = .444) but not at 50 m (P = .113, r = .399). Discussion: High BLC favored the performance of the highly trained female swimmer, especially in the 100-m event. Thus, training to promote anaerobic metabolism may enhance performance in short-distance swimming races, whereas the BLC may partly explain performance in such events.